A Correlation Between Retinal Nerve Fibre Layer Thickness And Axial Length In Non-Glaucomatous Myopes - Nasir, Erum; Haq, Intisar ul; Naeem, Badar ud din Athar; Asghar, Asfandyar; Nazir, Tehmina; Obaid, Naila (Journal of Rawalpindi Medical College, 2025)
Objective: To assess the correlation between retinal nerve fibre layer thickness and axial length in non-glaucomatous myopes. Methodology: This cross-sectional Study was conducted from May to October 2023 in the Department of Ophthalmology of Fauji Foundation Hospital, Rawalpindi. Eighty-five (85) patients with myopia 1D to −10D who visited the ophthalmology outpatient department underwent ocular examinations for the measurement of refraction, axial length, and OCT RNFL thickness. After pupillary dilatation, the thickness of the retinal nerve fibre layer surrounding the middle of the optic disc was assessed using optical coherence tomography (OCT). An automated computer program produced the analysis report of mean retinal nerve fibre layer thickness, which was then compared to the age-matched normative database that was integrated into 3D OCT. Results: The mean age was 18.88 + 5.4 years. The male: female ratio was almost the same. 47 (55.3%) were female and 38 (44.7%) were male. Most of the patients had moderate myopia, i.e. 48 (12.9%). The mean axial length was 25.89 + 1.42. The mean retinal nerve fibre layer (RNFL) thickness was 138.65 + 18.68. Pearson’s coefficient of correlation was -0.586. Conclusion: As axial length increases in myopic patients, the RNFL thickness decreases.